(untitled) (Modern education and development, 2025)
Erythrocytes, commonly known as red blood cells (RBCs), play an essential role in oxygen transport and the removal of carbon dioxide from the body. This article delves into the structure, functions, and biological significance of erythrocytes, highlighting key findings from relevant literature. Through a systematic analysis of various studies, this paper also discusses the latest advancements in understanding erythrocyte functionality and their broader implications for health and disease management.